Marketing Strategies and Perceived Service Quality Model Influencing Tourist Loyalty in Tourism of Pathum Thani Province - Pathomsirikul, Yaowapa (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
This research aimed to find the model of marketing strategies and perceived service quality influencing tourist loyalty in tourism of Pathum Thani Province. This research was quantitative, testing 2 groups of samples comprising 435 Thai visitors and 400 Foreign Tourists and visitors by using multi-stage sampling techniques. The data were collected by questionnaire. The statistics used in the research were descriptive statistics and the Structural Equation Modeling--SEM was used to test the marketing factors model. The findings found that (1) there were 2 variable factors, the marketing factors and perceived service quality of supporting tourism activities,. The latter directly affected Thai tourists’ satisfaction and indirectly affected the loyalty of Thai tourists. On the other hand, marketing factors and perceived service quality had both direct and indirect effects on the satisfaction and loyalty of foreign tourists. (2) The marketing strategies model for Thai tourists found that the most important factor was the tourism product and, in support of tourism activities, the service of the souvenir shop. In the marketing strategy model for foreign tourists, the most important marketing factor was Customer Relationship Management--CRM. In term of supporting tourism activities, the food service influenced their satisfaction. Loyalty of Thai tourists by word of mouth was the highest influence.